A case of type B insulin resistance presenting at a district general hospital. (9th June 2020) - Ramlochansingh, Osada; Surchi, Haval; Stears, Anna; O'Rahilly, Sir Stephen; Mimmack, Michael; Jayne, David
Abstract: Type B insulin resistance is a rare autoimmune condition with just over 100 cases described in the literature. We describe here the case of a young female who presented to our district general hospital with a rapid onset of profound insulin resistance not ameliorated by intensive insulin therapy. A previously fit and well 30‐year‐old woman was referred to hospital for hyperglycaemia without ketosis and clinical features consistent with diabetes. She had a normal BMI and no family history of note. Initially, treatment with oral medication was prescribed but due to a worsening of hyperglycaemia and HbA1c over the next few days, insulin therapy was introduced. It was quickly recognised that large doses of insulin given via subcutaneous and intravenous routes had little effect on her blood glucose with levels remaining well above 20mmol/L at maximum therapy. The presence of acanthosis nigricans along with cutaneous stigmata of connective tissue disease was noted and the case was referred to a specialist centre for further testing due to apparent severe insulin resistance. Antibody testing and further investigations were conducted revealing a final diagnosis of type B insulin resistance with an associated new diagnosis of systemic lupus erythematosus. Treatment of this patient's diabetes with immunosuppressive medication has been commenced with the hope of inducing remission. Copyright © 2020 John Wiley & Sons.